Efforts to Increase Students' Interest in Learning on PAI Subjects Through a Group Type Cooperative Learning Model Investigation (GI) Class V At SDN Ngronggo 3 - Addaroini, Rofi`'; Hidayah, Noer; Purwaningrum, Septiana (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This research aims to determine the implementation of Religious Education learning Islam using the Group Investigation type Cooperative Learning method for increase the learning interest of class V students at SDN Negeri 3 Kediri City. on the tree discussion of the attitude of simple living and sincere charity. This research is classroom action research, the research subjects of which are 23 class V students at SDN Ngronggo 3 Kediri City, consisting of 15 male students and 8 female student. Based on the research results, it shows that: (1) Cooperative Learning method type Group Investigation on PAI class V subjects at SDN Negeri 3 Kediri City was carried out well because with the Group Investigation type Cooperative Learning method educators can makes students more active in the learning process and does not feel bored, (2) The Group Investigation type Cooperative Learning method can be used increasing students' interest in learning in Class V PAI subjects at SDN Ngronggo 3 Kediri City, based on the results of the student questionnaire in pre-action, namely 58.7%, in cycle I namely 68.8%, while in cycle II the results of the student questionnaire were 75.5%.